HIỆU QUẢ ĐIỀU TRỊ TRẺ TỰ KỶ BẰNG PHƯƠNG PHÁP OXY CAO ÁP - Nguyễn, Phương Nam; Đỗ, Thị Bích Hà; Cao, Trung Thành; Trần, Đức Huynh (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
THE EFFECTS OF HYPERBARIC OXYGEN THERAPY IN TREATMENT FOR CHILDREN WITH AUTISM Fifty children with autism, 43 boys and 7 girls, aged from 2 to 10 (mean 4.9 ± 2), underwent 40 hyperbaric sessions of 60 minutes duration for each at 1.5 atmospheres and 100% oxygen. Outcome measures after 40 sessions were changed compared to pre-treatment scores and post-treatment scores for each child using the Autism Treatment Evaluation Checklist (ATEC). After 40 hyperbaric sessions, statistically significant improvements were observed on the ATEC scores (p < 0.001). The average improvement in all children were on the ATEC total score 21.8% (p < 0.001), speech/language/communication 15.8% (p < 0.001), sociability 21.9% (p < 0.001), sense/cognitive awareness 15.9% (p < 0.001), and health/physical fitness/behavior 31.6% (p < 0.001).